Standard specification for Composition Bronze for Ounce Metal Castings (American Society of Testing Materials, 2009)
This specification establishes requirements for an alloy having a composition of copper, tin, lead, and zinc, used for component castings of valves, flanges, and fittings. The common trade name of this alloy is 85-5-5-5; the correct identification is Copper Alloy UNS No. C83600.